Optimization by experimental design of precursor synthesis and radiolabeling of 2-iodo-L-phenylalanine, a novel amino acid for tumor imaging. - Kersemans, V; Kersemans, K; Cornelissen, B; Staelens, L; de Spiegeleer, B; Mertens, J; Slegers, G (2006)
Various radiolabeled amino acids show promising results in tumor detection, as applied in the management of cancer patients. We synthesized the precursor 2-iodo-L-phenylalanine for easier kit labeling of [123/125I]- 2-iodo-L-phenylalanine, using the Cu1+ -assisted nucleophilic halogen exchange. Precursor synthesis was optimized by experimental design: Eight parameters were initially screened by a quarter fractional design. The resulting most important parameters (i.e., temperature, CuSO4, NaI) were further optimized using a full three-factor, three-level factorial design. The final conclusion for the optimal values for temperature, reaction time, and concentration of 2-bromo-L-phenylalanine, NaI, CuSO4, SnSO4, C6H6O7, and C7H6O4 were 180 degrees C, 24 hours, 61 mM, 485 mM, 10 mM, 90 mM, 90 mM, and 100 mM, respectively. The yield was increased from 39% to consistently more than 74% 2-iodo-L-phenylalanine. Structure confirmation and quality control was performed by 1H-NMR, mass spectroscopy (MS), and high-performance liquid chromatography (HPLC) (reverse phase [RP] and chiral). No phenylalanine-related impurities or racemization was detected. Subsequent radioiodination of the obtained 2-iodo-L-phenylalanine was performed in kit conditions with n.c.a. Na123/125I, resulting in a labeling yield of > 98%. After Ag-membrane filtration, a radiochemical purity of > 99% was obtained. The Cu1+ -assisted nucleophilic exchange reaction allows both routine kit preparation and "cold" synthesis of 2-iodo-L-phenylalanine from 2-bromo-L-phenylalanine. The reaction presents an interesting alternative for a cumbersome multistep, stereo-specific synthesis.